1998
DOI: 10.1021/es9805223
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, Sources, and Fate of the Gasoline Oxygenate Methyl tert-Butyl Ether (MTBE) in a Multiple-Use Lake

Abstract: Discovery of the fuel additive methyl tert-butyl ether (MTBE) in drinking water supplies is of concern to public health officials, water suppliers, and the public. Despite recent policy decisions, few published studies exist on the concentrations, sources, and fate of MTBE in surface waters. The purpose of this study was to determine (1) the relative contribution of motorized watercraft as a source of MTBE, (2) its seasonal distribution, (3) loss from the water column, (4) the extent of vertical transport, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 9 publications
2
58
0
Order By: Relevance
“…This rate is smaller than that observed on Donner Lake by Reuter et al [8], which was 8 kg/day, and is similar to that observed on Perris Lake [9], which was 1.6 kg/day. The surface areas of the lakes differ, however, and Perris Lake has the highest rate when its surface area is accounted for.…”
Section: Daily Volatilization Ratesupporting
confidence: 73%
See 3 more Smart Citations
“…This rate is smaller than that observed on Donner Lake by Reuter et al [8], which was 8 kg/day, and is similar to that observed on Perris Lake [9], which was 1.6 kg/day. The surface areas of the lakes differ, however, and Perris Lake has the highest rate when its surface area is accounted for.…”
Section: Daily Volatilization Ratesupporting
confidence: 73%
“…As part of the National Water Quality Assessment (NAWQA) program conducted by the US Geological Survey (USGS), Squillace et al [3] found that MTBE was the second most frequently detected volatile organic compound (VOC) in ground water in nine areas across the country. MTBE also has been found in urban storm runoff and streams [4], lakes [5][6][7][8][9], and improper disposal of used motor oil [10]. MTBE in the atmosphere over southern New Jersey was monitored from 1996 to 1998 [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of MTBE in freshwater lakes and reservoirs indicated that detected MTBE concentrations ranged from <1 µg/L to as high as 88 µg/L and were typically associated with watercraft activity both spatially (e.g., marinas) and temporally (summer season/holiday weekends; 3,4,5). MTBE was also documented to occur in stormwater runoff at a low frequency of detection but ranging in concentration from 0.2 to 8.7 µg/L (6).…”
Section: Introductionmentioning
confidence: 99%